The PENERIMAAN DIRI PADA WBP DENGAN MASA HUKUMAN SEUMUR HIDUP DI LAPAS KELAS 1 SEMARANG - Satya Agum Kusuma; Emmanuel Satyo Yuwono (Fakultas Psikologi Universitas Kristen Satya Wacana, 2023)
Correctional Families are individuals who have received a guilty verdict from the court, resulting in that person having to lose their freedom of movement to carry out their criminal term in a penitentiary or state detention center. The purpose of this study was to find out the process of self-acceptance of prisoners who received life sentences in Class 1 prisons in Semarang. The type of research used by researchers in this study is a type of qualitative research with descriptive methods. The participants in this study were two prison inmates with life sentences in class 1 prisons in Semarang. The research data was obtained by interview and observation techniques. The results of this study include three main themes, namely gratitude for the current conditions, self-confidence to develop potential and social support as a form of self-acceptance.